La actividad física en el ámbito de la salud pública (1998)
ABSTRACT: Epidemiological research shows that sedentary lifestyle is a major factor in generating the new epidemic of chronic diseases, while physical activity is a protective factor, especially for a cardiovascular diseases. Promotion of health active lifestyles is a challenge for the new Public Health, because it requires the development of appropriate educational programs that are able to persuade individuals that excercise is beneficial for their health and that is also their responsability. Some additional arrangements are necessary in order to make physically active behaviors something socially acceptable and easy to practice.